Status Hukum Data Fisik dan Data Hukum Hak Milik Tanah Terendam oleh Air Rob di Kota Pekalongan - Salman Al Farisi; Siti As’adah Hijriwati; Ary Dwi Anjarini; Yustiana Dwirainaningsih; Irgie Khayati Ulwiyah (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
Land constitutes a limited asset whose availability does not significantly increase over time, thereby requiring strong legal assurance and protection. In Pekalongan City, recurrent tidal flooding (rob) has created uncertainties regarding land boundaries and the legal status of ownership rights. This research adopts a socio-legal approach with a qualitative descriptive design to examine these issues in depth, focusing on how legal norms interact with environmental changes and community practices. The findings indicate that inundated land cannot be legally regarded as extinguished or lost. Ownership rights remain attached to the land, even when its physical condition is altered by persistent flooding. Landowners can still identify and assert their territorial boundaries by installing higher and more adaptive boundary markers that accommodate fluctuating water levels. Furthermore, legal certainty over land ownership can be maintained through administrative mechanisms. These include applying for a Land Registration Certificate (SKPT) and requesting land re-measurement through the National Land Agency, which provides verified information on both juridical and physical aspects of the land. Thus, despite environmental challenges, the legal framework continues to offer avenues for protecting land rights and ensuring certainty for affected communities.